HUBUNGAN KUALITAS TIDUR DENGAN KESEHATAN MENTAL EMOSIONAL REMAJA KELAS X DAN XI DI SMK X MEDAN - Putri, Yessi Ananda; Wahyu, Afnijar (STIKes Murni Teguh, 2025)
Adolescence is an important period for developing social and emotional habits. Mental emotional is a condition in which a person undergoes psychological distress, there are psychological changes in certain circumstances but can recover back to normal, but these emotional mental problems if not properly dealt with will have a bad impact on the process of adolescent development. One of the long-term factors that can lead to adolescent emotional mental development is sleep problems such as sleep patterns. Especially the duration and quality of sleep, plays an important role inining health as lack of sleep increases the likelihood of an individual experiencing intense negative thoughts or feelings of emotional range. The aim is to identify the relationship between sleep quality and emotional mental health in adolescents. This type of research is quantitative which is a cross-sectional survey investigation using the Clusster Random Sampling technique. The total sample in this study was 205 students. Instruments were measured with a questionnaire. Analyze the data of this study using the Spearman test. Based on the results of the analysis obtained there is a p-value of 0.020 (< 0.05) which indicates that there is significant relationship between sleep quality and adolescent emotional mental health. It is recommended for future researchers to add different variables such as Factors related to emotional mental health.